Exploring Language Teacher Identity Work as Ethical Self‐Formation. (January 2017) - Miller, Elizabeth R.; Morgan, Brian; Medina, Adriana L.
Abstract : In this article, we treat language teacher identity as foundational to educational practice and see Foucault's (1983, 1997 ) notion of ethical self‐formation, and its adoption in teacher education research by Clarke (2008, 2009, 2010 ), as providing a potential vehicle for understanding the development of teacher agency and critical identity work. We use the 4 axes of Foucault's (1983 ) approach to ethical self‐formation, as captured in Clarke's (2009 ) "Diagram for Doing Identity Work, " in exploring a case study of an elementary reading and language arts teacher who worked in a multilingual inclusion classroom with exceptional (i.e., learning disabled) and mainstreamed students. We consider the relevance of how this teacher's identity developed over the course of 7 interviews, spanning 9 years, for teacher identity work in language teacher education (LTE). In doing so, we foreground the critical as well as the dangerous potential of all teachers' identity work and argue for the importance of nurturing teachers' reflective, action‐oriented identity practices as well as fostering a self‐awareness of language teachers as ethical subjects "acting on others" (Foucault, 1997, p. 262) even as they struggle within power relations that press upon educational practices and discourses.